Arts-Based Methods and Organizational Learning 2017
DOI: 10.1007/978-3-319-63808-9_10
|View full text |Cite
|
Sign up to set email alerts
|

Arts and Medicine: Connecting the Arts and Humanities to Professional Education

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…Several participants also believed that the awareness of and practices of medical ethics could be developed in later stages of the curriculum and clinical sessions. This result contradicts findings from another study, in which medical students from the same college appreciated and demonstrated their development of ethical thinking through a course focusing on medical humanity (Al Azmeh and Du, 2018). This divergence indicates that further communication is needed among medical educators and administrators regarding when and how to facilitate Ihsan and other needed competencies in the course of medical education.…”
Section: Discussioncontrasting
confidence: 63%
“…Several participants also believed that the awareness of and practices of medical ethics could be developed in later stages of the curriculum and clinical sessions. This result contradicts findings from another study, in which medical students from the same college appreciated and demonstrated their development of ethical thinking through a course focusing on medical humanity (Al Azmeh and Du, 2018). This divergence indicates that further communication is needed among medical educators and administrators regarding when and how to facilitate Ihsan and other needed competencies in the course of medical education.…”
Section: Discussioncontrasting
confidence: 63%